The Influence of Guided Inquiry Worksheets on Science Literacy and Learning Outcomes in Fourth-Grade Students - Sakina, Balik Sholikhatus; Ekawati, Ratna; Dasna, I Wayan (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to test the effectiveness of the use of Guided Inquiry-Based Student Worksheets (LKPD) in improving science literacy and science learning outcomes of grade 4 students on the topic of changes in the state of matter. A quantitative research approach was applied using a quasi-experimental design with a non-equivalent control group. Data collection techniques in this research used written tests, student scientific literacy questionnaires, observation, interviews, and data analysis. The population is 43 students in class 4 of SDN in two schools in one cluster, namely UPT SD Negeri Jeblog and UPT SD Negeri Kaweron 2. Statistical analysis included Two-Way Anova to evaluate differences between groups. The two-way ANOVA results showed significant differences in scientific literacy and learning outcomes between the experimental group (guided inquiry) and the control group (conventional method). The experimental group showed a greater increase in scientific literacy (average N-Gain = 33.28%) than the control group (average N-Gain = 23.45%). Learning outcomes also increased more significantly in the experimental group (average N-Gain = 20.69%) compared to the control group (average N-Gain = 11.23%), with a sig. 0.042 < 0.05. Hypothesis testing shows significant differences in scientific literacy and learning outcomes based on initial abilities and learning methods (sig. 0.000 < 0.05). The use of guided inquiry-based LKPD significantly improves scientific literacy and student learning outcomes, and is recommended for encouraging critical thinking and active participation in basic science education.